What can we learn from Airbnb data on tourist flows? A case study on Iceland - Cebeillac, Alexandre; Vaguet, Yvette (Espace populations sociétés, 2021)
Tourist flows are increasingly important – at least up to the covid-19 crisis - and the Arctic regions are no exception. In particular, Iceland is experiencing an unprecedented tourism boom that began a decade ago. This goes hand in hand with the development of online short-term rental platforms such as Airbnb. This article questions how public information on the Airbnb website can be used to study tourist flows, with Iceland as a case study. Using a program we developed, we collected information about the accommodation available on the platform, as well as any comments left by visitors.Each member’s profile also includes the place of residence declared by the user, which makes it possible to know the country of origin. We then compared this collected information with official statistical data. Airbnb, which is growing steadily, seems to be gaining ground on the classic hotel business. The Airbnb data reflects the officially recorded flows by country of origin. This makes the case for using this data for the Arctic region, for which statistical data is hard to find at a fine-scale. Les flux touristiques sont de plus en plus importants et les zones arctiques ne font pas exceptions. Plus particulièrement, l’Islande connaît un boom touristique sans précédents depuis une dizaine d’années. Ce dernier va de pair avec le développement de plateformes de locations de courtes durées en ligne, comme Airbnb. Cet article interroge l’intérêt des informations publiques sur le site Airbnb pour les recherches sur les flux touristiques. L’Islande constitue dans ce cadre, le cas d’application. À l’aide d’un programme que nous avons développé sous R, nous avons collecté les informations sur les logements disponibles sur la plateforme, ainsi que tous les commentaires laissés par les visiteurs.Le profil de chaque membre renseigne également le lieu du domicile déclaré par l’utilisateur, ce qui permet de connaître le pays d’origine. Nous avons ensuite comparé ces informations récoltées aux données statistiques officielles. Airbnb, en ...